Sorption Kinetics of CH4 and CO2 Diffusion in Coal: Theoretical and Experimental Study - Naveen, P.; Asif, M.; Ojha, K.; Panigrahi, D.; Vuthaluru, Hari (American Chemical Society, 2017)
© 2017 American Chemical Society. Experimental and theoretical analyses with empirical correlations were framed for diffusion of gas species CH 4 and CO 2 in coal samples from Jharia coal fields, India, considering the intrinsic pore parameters. Coefficient of diffusion (D) and diffusivity (D eff ) for a single and binary component coal-gas system were estimated by adopting unipore gas kinetic models for gas flow on the integration of Fick's law and Langmuir relation. The rigorous study was carried out in estimating crossover pressure, which is dominant in distinguishing the flow regime for two primary types of diffusion: Knudsen and molecular as well as the transition between two regimes. Investigation reveals that experimental values of coefficients of diffusion of CH 4 and CO 2 in random homogeneous isotropic sphere packing of coal samples are in good agreement with the results of theoretical calculations. For the pressure range investigated, variation of coefficient of diffusion was found to follow a dual nature with a stable trend at pressures above 3500 kPa and an increasing trend for lower pressures. The practical implication of the investigation for the pressures that are characteristically encountered in the Jharia coalfields is a positive finding for the concomitant recovery of coalbed methane with CO 2 sequestration. Additionally, the dynamic relation between sorption-diffusion reveals that the coefficient of diffusion significantly depends on the pore structure and pore size distribution, exhibiting a negative relationship with pressure variation.